2020
DOI: 10.1186/s12891-020-03447-3
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in articular cartilage T2 star relaxation time following mechanical disorders: in vivo canine supraspinatus tendon resection models

Abstract: Background: The role of altered joint mechanics on cartilage degeneration in in vivo models has not been studied successfully due to a lack of pre-injury information. We aimed 1) to develop an accurate in vivo canine model to measure the changes in joint loading and T2 star (T2*) relaxation time before and after unilateral supraspinatus tendon resections, and 2) to find the relationship between regional variations in articular cartilage loading patterns and T2* relaxation time distributions. Methods: Rigid mar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In the instance of T2* relaxometry, our findings are consistent with Lee et al findings; in their study also they also found that larger T2* values corresponded to increased cartilage degradation in a canine model. 26 However, in a research by Mankin et al, T2* values declined as cartilage deterioration progressed. 27 …”
Section: Discussionmentioning
confidence: 92%
“…In the instance of T2* relaxometry, our findings are consistent with Lee et al findings; in their study also they also found that larger T2* values corresponded to increased cartilage degradation in a canine model. 26 However, in a research by Mankin et al, T2* values declined as cartilage deterioration progressed. 27 …”
Section: Discussionmentioning
confidence: 92%
“…Magnetic resonance imaging (MRI) is a widely used technique to image knee anatomy [11], and quantitative relaxometry is sensitive to tissue composition including changes in water content, proteoglycans, and collagen fiber orientation [12]. Both transverse relaxation time ( T 2 ) and effective T 2 ( T 2 * ) have been shown to correlate to cartilage degeneration [13]. An increase in the T 2 correlates with damage to articular cartilage, signifying deterioration of the collagen network and increase in the water content [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Transection of the supraspinatus tendon can lead to increased adduction and lateral shoulder subluxation without substantial abduction, as well as changes in articular cartilage contact strain that are associated with corresponding changes in the T2* relaxation time. 2 As dogs disproportionately transfer more body weight to the thoracic limb musculature, trauma to the supraspinatus is of interest, in that injury may be anticipated to cause substantial lameness. However, identifying supraspinatus injury of the muscle or tendon has been a diagnostic challenge in veterinary medicine, as early imaging for most lameness had been limited to radiographs.…”
Section: Introductionmentioning
confidence: 99%